2021
DOI: 10.1038/s41598-021-93457-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic variation of ultraviolet–visible-infrared spectral wavelengths of bovine meat

Abstract: Spectroscopic predictions can be used for the genetic improvement of meat quality traits in cattle. No information is however available on the genetics of meat absorbance spectra. This research investigated the phenotypic variation and the heritability of meat absorbance spectra at individual wavelengths in the ultraviolet–visible and near-infrared region (UV–Vis-NIR) obtained with portable spectrometers. Five spectra per instrument were taken on the ribeye surface of 1185 Piemontese young bulls from 93 farms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The overlapping region may contain the most influential bands for predicting root starch content. Bittante et al (2021) made a similar observation, emphasizing the importance of capturing the most informative portion of the spectrum. Rukundo et al (2021) reported that the limited spectral range of the smartphone NIR spectrometer used in their study did not affect model performance.…”
Section: Instrument Comparisonmentioning
confidence: 61%
See 1 more Smart Citation
“…The overlapping region may contain the most influential bands for predicting root starch content. Bittante et al (2021) made a similar observation, emphasizing the importance of capturing the most informative portion of the spectrum. Rukundo et al (2021) reported that the limited spectral range of the smartphone NIR spectrometer used in their study did not affect model performance.…”
Section: Instrument Comparisonmentioning
confidence: 61%
“…The overlapping region may contain the most influential bands for predicting root starch content. Bittante et al. (2021) made a similar observation, emphasizing the importance of capturing the most informative portion of the spectrum.…”
Section: Instrument Comparisonmentioning
confidence: 61%